Observance of national ethics codes of medical research in undergraduate doctoral dissertations in the Faculty of Dentistry, Islamic Azad University, Khorasgan Branch in 2004-2009 - Arash Ghodousi; Vahid Esfahanian; Sayed Mohammad Razavi; Afrasiab Ghaedifar; Elham Zamani Pozveh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Observance of ethical codes in dental research has received little attention. This research aims to evaluate observance of national research ethics codes in research proceedings of doctoral dissertations in the Faculty of Dentistry, Islamic Azad University, Khorasgan Branch in 2004-2009.Materials and Methods: This descriptive-analytical research was conducted on 200 doctoral dissertations. National ethics codes in medical research were evaluated by two researchers. Data was recorded in specially designed forms and analyzed by descriptive statistical tests.Result: In all the dissertations - human and non-human research studies - all the ethics codes in relation to confidentiality of data, conformity with cultural and religious principles, and the possibility of side effects for the subjects, had been observed. In relation to human studies 89 dissertations lacked informed written consent forms, with oral consent taken in 83% of cases. In only 14 cases (15.7%) of the participants were aware of their right to exclude themselves whenever they wished. In laboratory research dissertations (111 cases) in only 47% of cases all the ethics codes had been observed.Conclusion: All the sixteen medical ethics codes in human research had not been observed in any of the research protocols; in laboratory research, almost half of the protocols had observed scientific ethics principles (5 codes), which might be attributed to a lack of importance of registration of ethics codes in research protocols despite the fact that researchers usually observe them in dissertation protocols. Key words: Clinical trial, Codes of Ethics, Informed consent, Laboratory research.